1982
DOI: 10.1017/s0142716400004276
|View full text |Cite
|
Sign up to set email alerts
|

Use of orthographic structure by deaf adults: Recognition of fingerspelled words

Abstract: Deaf adults' access to English word structure was tested in a task requiring letter report for fingerspelled words, orthographically regular nonsense words (pseudowords), and orthographically irregular nonsense words (nonwords). Deaf subjects, like hearing subjects, were sensitive to orthographic structure as indicated by accuracy of letter report: Letters of words were reported most accurately, while letters of pseudowords were reported more accurately than letters of nonwords. Analysis of errors on letter re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…There are indications that syllables, in some form, influence deaf performance, either from syllable counting (Sterne & Goswami, 2000) or from segmentation tasks (Olson & Nickerson, 2001;Transler, Leybaert, & Gombert, 1999). More directly related to our hypotheses, several studies have found that deaf students are worse at perceiving or remembering illegal nonwords 388 OLSON AND CARAMAZZA than legal nonwords in reading, writing, or fingerspelling tasks (Aaron, Keetay, Boyd, Palmatier, & Wacks, 1998;Gibson, Shurcliff, & Yonas, 1970;Hanson, 1982bHanson, , 1986. In a previous study of deaf spelling errors, Hanson, Shankweiler, and Fischer (1983) noted that the overwhelming majority of deaf spelling errors did not violate orthographic constraints (91.7% of the hearing responses and 96% of the deaf spellings were orthographically legal-although deaf spelling may not always conform to this pattern, see Sutcliffe, Dowker, & Campbell, 1999).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…There are indications that syllables, in some form, influence deaf performance, either from syllable counting (Sterne & Goswami, 2000) or from segmentation tasks (Olson & Nickerson, 2001;Transler, Leybaert, & Gombert, 1999). More directly related to our hypotheses, several studies have found that deaf students are worse at perceiving or remembering illegal nonwords 388 OLSON AND CARAMAZZA than legal nonwords in reading, writing, or fingerspelling tasks (Aaron, Keetay, Boyd, Palmatier, & Wacks, 1998;Gibson, Shurcliff, & Yonas, 1970;Hanson, 1982bHanson, , 1986. In a previous study of deaf spelling errors, Hanson, Shankweiler, and Fischer (1983) noted that the overwhelming majority of deaf spelling errors did not violate orthographic constraints (91.7% of the hearing responses and 96% of the deaf spellings were orthographically legal-although deaf spelling may not always conform to this pattern, see Sutcliffe, Dowker, & Campbell, 1999).…”
mentioning
confidence: 64%
“…Previous studies of the deaf have not been able to explain effects of orthographic regularity using letter frequency (Gibson et al, 1970;Hanson, 1982bHanson, , 1986, but a limited range of frequency measures has been considered, and frequency has not been central to these studies. We test a wider variety of measures.…”
mentioning
confidence: 99%
“…This interpretation would be in line with the data obtained by Hanson. This author systematically observed that deaf adults were sensitive to orthographic structure during spelling (Hanson, Shankweiler, & Fisher, 1983), during a letter report (Hanson, 1982), and during letter detection and word-like judgment (Hanson, 1986). She observed that even deaf adults with poor speech were sensitive to orthographic structure, and that their use of positional frequency information was the same as in hearing people (Hanson, 1986).…”
Section: Sensitivity To Syllabic Structure and Syllabic Boundariesmentioning
confidence: 99%
“…), they can elicit information indirectly through conversation, they can look it up in textbooks and grammars, and they can acquire it from experience with the language, not only listening experience, but also reading, whatever the topic or material. Written language contains a wealth of information about segmental phonological regularities (and in English, this information is certainly of use to L1 users who have been deaf for their entire life; Hanson, 1982; Hanson, Shankweiler, & Fischer, 1983).…”
mentioning
confidence: 99%